Numerical simulation of droplet-based microfluidics - Liu, Jing (2012)
This paper discusses the features and applications of interface tracking techniques for modeling droplet-based microfluidics. The paper reviews the state of the art of methods for tracking and capturing the interface. These methods are categorized as the implicit and the explicit methods. The explicit methods need to reconstruct the interface by reconnecting the markers on the interface. The implicit techniques implicitly describe the interface as a simple function. Thus, complicated topological changes of interface can be handled naturally and automatically. The implicit methods reviewed in this paper are the volume-of-fluid method, the phase-field method, the Lattice-Boltzmann method and the level-set method. The explicit methods mainly include the boundary-integral methods and the tracking methods.